2023
DOI: 10.1021/acsami.2c21971
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Stability of Mg2Si0.6Sn0.4 under Oxidation Conditions

Abstract: The use of Mg 2 Si 0.6 Sn 0.4 under air in thermoelectric modules in the mid-temperature range of 400−600 °C is linked to its ability to resist oxidation. In this study, oxidation experiments performed at 400 °C under air evidenced the stability of the material, either under static conditions (up to 100 h) or under severe heating-cooling cyclic conditions (up to 400 cycles), showing its ability to be used in a reliable way at this temperature. By combining thermogravimetry, scanning electron microscopy, temper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 56 publications
(81 reference statements)
0
2
0
Order By: Relevance
“…A complete description of their design, assembly, and TE performances has been reported in ref . Detailed studies of the n -type and p -type raw materials and legs properties, such as microstructure, chemical composition, mechanical properties, and stability under air, were already reported in our last papers. ,,,, In the rest of this article, we will refer to MnSi 1.77 as HMS and Mg 2 Si 0.6 Sn 0.4 as Mg 2 (Si,Sn).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A complete description of their design, assembly, and TE performances has been reported in ref . Detailed studies of the n -type and p -type raw materials and legs properties, such as microstructure, chemical composition, mechanical properties, and stability under air, were already reported in our last papers. ,,,, In the rest of this article, we will refer to MnSi 1.77 as HMS and Mg 2 Si 0.6 Sn 0.4 as Mg 2 (Si,Sn).…”
Section: Methodsmentioning
confidence: 99%
“…They are eco-friendly and are composed of abundant and cheap materials while exhibiting a high TE performance. Many studies have been focused on the manufacture and development of silicium-based TEGs. Stability problems caused by oxidation may however hinder the use of the Mg 2 (Si,Sn) solid solutions in long-term applications at high temperature. On the other hand, HMS exhibit good chemical, thermal, and mechanical stability. In a previous work, we have shown that silicide-based thermoelectric modules (TEM), composed of n -type (Mg 2 Si 0.6 Sn 0.4 ) and p -type (MnSi 1.77 ) legs and manufactured on the base of a “half skeleton”, exhibit no deterioration during the performance tests carried out up to 450 °C. An average maximum power output of 0.37 W, corresponding to a power density of 0.95 W/cm 2 , has been achieved for a temperature difference of 400 °C (hot side temperature of 450 °C).…”
Section: Introductionmentioning
confidence: 99%